2015
DOI: 10.1111/aas.12606
|View full text |Cite
|
Sign up to set email alerts
|

Asphyxia causes ultrasonographic D‐shaping of the left ventricle – an experimental porcine study

Abstract: The early and transient acute dilatation of the RV, coinciding with D-shaping of the LV and decrease in LV end-diastolic area seen in our study represent a combination of ultrasonographic characteristics normally attributed to pulmonary embolism. Early changes in ventricular chamber sizes and shape with septal flattening related to asphyxia can occur, but appear to be transient and disappear as circulatory collapse progresses, in an animal model. Despite this, asphyxia may represent a cause of ultrasonographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…We predefined an increase in the LV end‐diastolic eccentricity index (primary end point) from 1.0 to 1.3 to be the minimal increase of clinical relevance. Given this effect and standard deviations extracted from previously published data of 0.2 and 0.3, respectively, a nonparametric power analysis based on a before‐after situation showed a need for 9 piglets (α = .05; power = 0.8). To compensate for unforeseen sources of variation, we decided to include 10 piglets in the intervention group.…”
Section: Methodsmentioning
confidence: 78%
See 2 more Smart Citations
“…We predefined an increase in the LV end‐diastolic eccentricity index (primary end point) from 1.0 to 1.3 to be the minimal increase of clinical relevance. Given this effect and standard deviations extracted from previously published data of 0.2 and 0.3, respectively, a nonparametric power analysis based on a before‐after situation showed a need for 9 piglets (α = .05; power = 0.8). To compensate for unforeseen sources of variation, we decided to include 10 piglets in the intervention group.…”
Section: Methodsmentioning
confidence: 78%
“…The LV area change was calculated as (LV end‐diastolic area – LV end‐systolic area)/LV end‐diastolic area and expressed as a percentage. Two inner diameters of the LV, perpendicular and parallel to the interventricular septum, were calipered at end diastole for derivation of the LV eccentricity index at both end diastole and end systole as previously explained in detail . All sonographic analyses were performed by a single observer and repeated by a second observer for calculation of interobserver variation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical settings, D‐shaping of the LV is often attributed to pulmonary embolism, as explained previously. However, Netzer's study and several porcine studies have shown that septal D‐shaping (Figure ) may occur as a response to hypoxic pulmonary vasoconstriction, with or without hypercapnia, as well. In these studies, RV dimensions normalized within minutes after re‐oxygenation.…”
Section: Echocardiographic Changes Due To Acute Respiratory Failurementioning
confidence: 99%
“…Parasternal short‐axis views of an anesthetized, porcine heart at baseline (A) and after 90 s of asphyxia induced by ventilator respiratory hold (B). Flattening of the interventricular septum indicates an acute pressure increase in the right‐sided circulation LV = left ventricle; RV = right ventricle…”
Section: Echocardiographic Changes Due To Acute Respiratory Failurementioning
confidence: 99%